Evaluating the impact of an integrated KIPP and positive psychology course on university students’ psychological well-being in China: a mixed-methods study - Liu, Tzu-Hsuan; Sun, Huiwen (Frontiers in Psychology, 2025)
IntroductionThis study evaluated the impact of an integrated general education course—Building a Flourishing Life: Integrating KIPP and Positive Psychology—on the psychological well-being of university students in China. Drawing on the dual frameworks of the Knowledge is Power Program (KIPP) and the VIA character strengths model, the intervention aimed to promote happiness and reduce depression and anxiety.MethodsUsing a mixed-methods approach, we collected pre- and post-intervention survey data (N = 116), performed fuzzy-set Qualitative Comparative Analysis (fsQCA) to identify configurational pathways, and applied directed content analysis to qualitative interview responses.ResultsQuantitative results showed significant increases in happiness and decreases in depression and anxiety, which highlighted the additive and substitutive roles of strengths-based practices. Qualitative findings reinforced these outcomes. The fsQCA findings showed that no single module was necessary for the observed improvements in psychological well-being. Instead, multiple combinations of modules functioned synergistically.ConclusionThis study contributes to the growing literature on culturally responsive positive education and addresses recent critiques regarding the contextualization of psychological interventions in higher education.